Satisfying psychological needs and its relationship to the level of marital compatibility according to Maslow’s theory among a sample of married men in Jeddah (The International Journal of Educational Sciences and Arts, 2026)
This study aimed to examine the relationship between the fulfillment of psychological needs and marital adjustment according to Maslow’s theory among a sample of married men in the city of Jeddah. The study adopted the descriptive correlational approach and was conducted on a sample of 439 married men selected using the simple random sampling method. To achieve the objectives of the study, the researcher developed two scales: a psychological needs scale consisting of psychological and social dimensions, and a marital adjustment scale comprising intellectual, emotional, and familial dimensions. The psychometric properties of both instruments were verified, and appropriate statistical methods were employed, such as Pearson correlation coefficient, Mann-Whitney test, and Kruskal-Wallis test. The results revealed a statistically significant positive correlation between the fulfillment of psychological needs and marital adjustment among the sample. The findings also indicated that the level of marital adjustment among married men in Jeddah was high. Additionally, significant differences were found in the level of psychological needs fulfillment based on age and years of marriage, while no statistically significant differences were found in marital adjustment levels based on the same variables. The study recommends the importance of promoting marital counseling, focusing on fulfilling psychological needs, and raising public awareness through social media about the significance of psychological well-being for spouses and its role in building a healthy, well-adjusted family.
Keywords: Psychological Needs; Marital Adjustment; Married Men; Maslow’s Theory; Jeddah City